INVESTMENT OPTIMIZATION FOR GOLD VEIN MINING WITH OPTIONAL CUT-OFF-GRADE AND FUZZY REAL OPTION METHODS : CASE STUDY OF VEIN KUBANG CICAU PT ANTAM TBK PONGKOR - Sibarani, Sariuly
PT Antam, Tbk UBPE Pongkor vein Kubang Cicau B will end at the level of 475 masl. This is because, PT Antam, Tbk UBPE Pongkor is currently mining below the level of the Cikaniki river which is at the level of 500 masl. Pongkor mining has a great risk and has the potential to harm the company if it continues mining investment to a level < 475 masl. The distribution of vein Kubang Cicau B and mining difficulties at levels <475 masl are increasing as mining depth increases. PT Antam, Tbk. UBPE Pongkor evaluates the economic value using break even cutoff grade (BECOG) and discounted cash flow. Both methods have weaknesses in determining NPV because they ignore the potential for optimum cut-off grade, flexibility in management decisions and fluctuations in price changes that may occur over the life of the mine. The need for a more detailed assessment of the cutoff grade that can maximize the economic value of the production of an ore body with the optimum cut-off grade method. Furthermore, it is necessary to evaluate the economic value of the ore body's production by including the uncertainty aspect, namely the selling price whose value is uncertain due to the influence of commodity supply and demand in the global market and other factors with the fuzzy real option method. The cut-off grade value of the optimum cut-off grade is 3.01 ppm. An economic evaluation of vein Kubang Cicau B on actual fix cost using the DCF method yields -11,191,507, so the project cannot be continued. With the fuzzy real option method of PT Antam, Tbk UBPE Pongkor will get an increase in NPV called expanded fuzzy NPV (EFNPV)> 0 if it waits for 26 months with the current price as a start, waits 31 months with an average price as the initial price, or at the end of the IUP the OP reduced the fix cost by 50% at the current price as a start.Keywords: vein, discounted cash flow, Break Even Cut-Off, optimum cut-off grade, fuzzy real options, expended fuzzy NPV.